Rho-Associated Kinase Inhibitor Immortalizes Rat Nucleus Pulposus and Annulus Fibrosus Cells: Establishment of Intervertebral Disc Cell Lines With Novel Approaches. Issue 5 (March 2016) - Oh, Chun-do; Im, Hee-Jeong; Suh, Joon; Chee, Ana; An, Howard; Chen, Di
Abstract : Study Design: Establishment of immortalized cell lines derived from rat intervertebral disc cells by Rho-associated kinase (ROCK) inhibitor, Y-27632. Objective: To determine whether rat nucleus pulposus (NP) and annulus fibrosus (AF) cells could be immortalized, retain their phenotype, and used as cell lines for in vitro cell biology. Summary of Background Data: Intervertebral disc degeneration is a major factor for most low-back pain. However, the mechanism of the disease is not well understood by the limitation to obtain sufficient amounts of primary disc cells. Therefore, the establishment of disc cell lines will help in vitro molecular signaling studies to understand the mechanism of degenerative disc disease. Methods: Cells were isolated from the NP and AF tissues of lumbar discs of adult Sprague Dawley rat. Tissues were digested and cultured with DMEM/Ham's F-12 (1:1) and 20% FBS and antibiotics. From day 3, cells were grown in the presence of 10 μM Y-27632, a well-characterized inhibitor of the ROCK, and subcultured by trypsinization, passaging them 1:3 onto 100 mm culture dishes. Morphologic and genetic analyses were performed on the different passaged cells. Results: ROCK inhibitor successfully immortalized rat NP and AF cells. They passaged for over 50 generations with sustained expression levels of several NP and AF cell markers. In addition, they retained phenotypic features similar to the primary parental NP and AF cells when the cells were challenged with different cytokines and growth factors. Conclusion: We established immortalized rat NP and AF cell lines using a method of treating cells with ROCK inhibitor Y-27632 and demonstrated that these immortalized cells retain the properties of primary cells and could serve as useful tools for in vitro signaling studies or drug screening studies to develop novel therapeutic strategies. Level of Evidence: N/A